(untitled) (Journal of Atomic and Molecular Sciences, 2021)
Both non-homogenization treatment Zr, Ga addition and ternary Strip Casting alloy flakes can be used to prepare anisotropy HDDR NdFeB magnetic powders. This illustrates that anisotropy formation of magnetic powders neither depends on element addition nor depends on homogenization heat treatment of SC flakes. But the HDDR process procedure also plays an important role in anisotropy inducement. Highly anisotropic magnetic powders are attributed to rapid disproportionation reaction course, slow desorption-recombination reaction course, and optimum recombination hydrogen pressure during HDDR procedure process. This paper will provide an important guidance for preparing highly anisotropy magnetic powders with low cost.